Should all anticoagulated patients with head injury receive a CT scan? Decision-analysis modelling of an observational cohort. Issue 12 (13th December 2016) - Kuczawski, Maxine; Stevenson, Matt; Goodacre, Steve; Teare, M Dawn; Ramlakhan, Shammi; Morris, Francis; Mason, Suzanne
Abstract : Objectives: It is not currently clear whether all anticoagulated patients with a head injury should receive CT scanning or only those with evidence of traumatic brain injury (eg, loss of consciousness or amnesia). We aimed to determine the cost-effectiveness of CT for all compared with selective CT use for anticoagulated patients with a head injury. Design: Decision-analysis modelling of data from a multicentre observational study. Setting: 33 emergency departments in England and Scotland. Participants: 3566 adults (aged ≥16 years) who had suffered blunt head injury, were taking warfarin and underwent selective CT scanning. Main outcome measures: Estimated expected benefits in terms of quality-adjusted life years (QALYs) were the entire cohort to receive a CT scan; estimated increased costs of CT and also the potential cost implications associated with patient survival and improved health. These values were used to estimate the cost per QALY of implementing a strategy of CT for all patients compared with observed practice based on guidelines recommending selective CT use. Results: Of the 1420 of 3534 patients (40%) who did not receive a CT scan, 7 (0.5%) suffered a potentially avoidable head injury-related adverse outcome. If CT scanning had been performed in all patients, appropriate treatment could have gained 3.41 additional QALYs but would have incurred £193 149 additional treatment costs and £130 683 additional CT costs. The incremental cost-effectiveness ratio of £94 895/QALY gained for unselective compared with selective CT use is markedly above the threshold of £20–30 000/QALY used by the UK National Institute for Care Excellence to determine cost-effectiveness. Conclusions: CT scanning for all anticoagulated patients with head injury is not cost-effective compared with selective use of CT scanning based on guidelines recommending scanning only for those with evidence of traumatic brain injury. Trial registration number: NCT 02461498.